The Quality of Health Care in Italy: the Osservasalute Report 2005 (Italian Journal of Public Health, 2005)
The Osservasalute Report intends to provide independent information of a high level on health and quality of care in the Italian Regions and to provide information for supporting decisions and choices of health programs and resource allocation.The Osservasalute Report represents a pilot experience in using regional data and when possible using data at provincial or local health trust level. The report is based on an in-depth analysis of the geographic variations and regional differences and the study allows for the identification of ideal performances that every region should strive to achieve.Comparable regional data was compiled from different sources in order to use them for monitoring and benchmarking the performance of regional health and healthcare systems.